Just plug 7 in for x and prove that both sides are equal:
-3(x-4) = 12- 7(x-4)
-3(7-4) = 12- 7(7-4)
-3(3) = 12- 7(3)
-9 = 12- 21
-9 = -9
2007-07-17 07:35:42
·
answer #1
·
answered by Mitchell . 5
·
0⤊
0⤋
I see the person before me missed the first four words of the question.
To verify the solution without solving the equation, just plug x=7 into the equation. If both sides turn out to be the same, then x=7 is a solution.
-3(7-4) = 12 - 7(7-4)
-3(3) = 12 - 7(3)
-9 = 12 - 21
-9 = -9
2007-07-17 14:32:42
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
If a number is said to be a solution to an equation, then substituting that number into the equation will result in the equation "working", or being a mathematically correct statement.
For this equation, simply substitute 7 for x.
-3(7-4)=12-7(7-4)
-3(3) =12-7(3)
-9 = 12 - 21
-9 = -9
This procedure is especially useful when you have to solve equations that contain the variable, or unknown, under a square root sign. In these instances, you square both sides to get rid of the square root sign. Any negative terms become positive as a result, and the resulting solutions ALWAYS have to be substituted back into the original equation to verify that it is an acceptable answer.
Good luck with your math!
2007-07-17 14:44:17
·
answer #3
·
answered by Grampedo 7
·
0⤊
0⤋
just plug 7 into it
-3 (7 -4) = -3 * (3) = -9
12 - 7(7-4) = 12 - 7 * 3 =-9
since the left side = the right side
7 is the solution
2007-07-17 14:32:49
·
answer #4
·
answered by buoisang 4
·
0⤊
0⤋
Simply, put in 7 in place of x on both sides of the equal sign and both sides should arrive at the same answer. If it does, that means that 7 is the solution, If it doesn't, 7 is not the correct solution.
2007-07-17 14:36:38
·
answer #5
·
answered by HarpoonDragoon 3
·
0⤊
0⤋
LHS
-3(7 - 4)
- 3 x 3
- 9
RHS
12 - 7 x (3)
12 - 21
- 9
LHS = RHS so 7 is the solution.
2007-07-17 14:41:26
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
7 is the only number there which cannot divide 12
2007-07-17 14:33:13
·
answer #7
·
answered by cherry 2
·
0⤊
1⤋
simplify:
-3x + 12 = 12 - 7x + 28
combine like terms:
4x = 28
x = 7
2007-07-17 14:32:27
·
answer #8
·
answered by miggitymaggz 5
·
0⤊
2⤋
I like Geezah's answer.
2007-07-17 14:40:27
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋